2014
DOI: 10.4103/0019-5278.146911
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of occupational injuries at workplace among welders in coastal south India

Abstract: Background:Injuries among welders are an important health issue in metal industries at global level. The study aimed to assess the prevalence and pattern of injuries and its possible associated risk factors among welders.Materials and Methods:A cross-sectional study was conducted among 209 welders in metal industries of Puducherry, coastal south India. Data regarding all types of injuries during the past 1 year were collected by administering a pre-designed questionnaire. The various risk factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
45
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 12 publications
12
45
1
1
Order By: Relevance
“…6 More than 1/3 rd of the welders in this study who reported having sustained injury in past 12 months, reported injury more than once. This is also reported from India 13 and Africa. 6 The use of at least one PPE in this study was high, compared to the finding from eastern Nepal.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…6 More than 1/3 rd of the welders in this study who reported having sustained injury in past 12 months, reported injury more than once. This is also reported from India 13 and Africa. 6 The use of at least one PPE in this study was high, compared to the finding from eastern Nepal.…”
Section: Discussionsupporting
confidence: 77%
“…12,13 Welding as a profession predominantly undertaken by males globally. The age group of the welders is similar with studies in Nepal and Nigeria, where a major proportion of welders are of younger age.…”
Section: Discussionmentioning
confidence: 99%
“…3000. 6 Kumar SG et al reported that the welders were working for less than 8 hours per day whereas our study reveals that the welders are working for more than 8 hours per day (8 to 12 hours). 6 This difference may be due to the different work cultures present in various parts of the country and the negligence of the state in enforcing work related regulations in this unorganized sector.…”
Section: Discussioncontrasting
confidence: 49%
“…4 In 2003, it was estimated that over a million workers between 20 and 40 years old worldwide, were employed in the welding industry. 5,6 Welders and those working in the vicinity, are exposed to toxic emissions recognized as health hazards. For example, welding fumes containing manganese particles have shown to result in serious neurotoxic effects.…”
Section: Introductionmentioning
confidence: 99%